Invasive lung infection by Scedosporium apiospermum in an immunocompetent individual - David Agatha; Krishnan Usha Krishnan; Ved-achalam Dillirani; Rangam Selvi (Wolters Kluwer Medknow Publications, 2014)
Scedosporium apiospermum previously known as Monospermum apiospermum is a ubiquitous fungus found in soil, polluted water and sewage. It causes broad spectrum of diseases, including soft tissue infections, septic arthritis, osteomyelitis, ophthalmic infections, sinusitis, pneumonia, meningitis, brain abscesses, endocarditis and disseminated infection. In recent years, it has been shown to be pathogenic for both immunocompetent and immunosuppressed patients. It is a significant opportunist with very high levels of antifungal resistance. We report here a case of invasive lung infection due to S. apiospermum in an immunocompetent patient who responded to antifungal therapy and surgical treatment.